Fabrication of CNT based electronic devices - Ong, Kai Tat. (2009)
Carbon nanotubes (CNTs) are materials that are close to ideal one-dimensional system, with diameters in the range 1-2 nm and length up to several millimeters making them excellent sensors for studying biological and chemical systems. For single-walled nanotubes (SWNTs) every atom is on the surface and exposed to the environment thus even small changes in the charge environment can cause drastic change to their electrical properties. Field-effect transistors (FETs) using SWNTs as the conducting channel were used to conduct biomolecules sensing in an electrolyte solution.